ANNE OF GREEN GABLES - Montgomery, L. M., 1874-1942, (Lucy Maud); Distefano, Elena (Leicester, United Kingdom : Sweet Cherry Publishing, 2018)
When Anne Shirley 'erupts' into their lives, the Cuthberts little guess how fond they will become of the skinny, red-haired orphan. Both entertained and exasperated by her constant chatter and imaginings, they soon find it hard to remember what Green Gables was like without its irrepressible adopted daughter.
First published in 1908
Keywords: Shirley, Anne, -- (Fictitious character)| -- Juvenile fiction; Orphans -- Juvenile fiction; Country life -- Juvenile fiction. -- Prince Edward Island; Friendship -- Juvenile fiction; Children's stories; Fiction